Studies on Corrosion Behavior of Mg-Al-Zn-RE Cast Alloy with Powder-Coated Al and CED Mg by Salt Spray Test, Immersion Test, and Electrochemical Test. (13th July 2022) - Krishnan, R.; Manivannan, S.; Patel, Praveen Bhai; Patil, Pravin P; Venkatesh, R.; L, Natrayan; Thanappan, Subash
Abstract : Cathodic electrodeposition (CED) was used to coat the cast magnesium alloy Mg-9Al-1Zn-xRE with aluminum powder and epoxy. Immersion and salt spray tests (ASTM B117) at room temperature for a total of 240 hours have been performed to assess the corrosion performances of AZ91D magnesium alloy. At each 24-hour interval, the samples were checked for any damage or deterioration of the coating surface morphology. The X-ray diffraction (XRD) analysis confirmed the phases, and scanning electron microscopy (SEM) with EDS analysis confirmed the phase composition. The electrochemical results show that CED epoxy coatings have superior adhesiveness and corrosion resistance compared to powder-coated aluminum and cast magnesium. The salt spray and immersion test results also confirm that CED epoxy coating exhibits good corrosion resistance.